That Which Has Been Bequeathed to Us: Stories in Educational Histories - Christou, Theodore Michael (TAWARIKH, 2010)
ABSTRACT: This paper outlines the concepts used by John Dewey to articulate the importance of relating instruction to personal and broader experience.Â In other words, a Deweyan interpretation of the terms âcorrelationâ (in part, the integration of disciplinary study and human experience) and ârecapitulationâ (in part, we can come to understand the evolution of human knowledge) hold the key to educational historyâs resuscitation and reintegration into Ontario teacher education. Further, this paper argues that history of education, which is presently on the periphery of teacher education curricula across Canada, is vital.Â The key to justifying and securing a place for humanistic disciplines in professional teacher preparation programs, which are highly influenced by accountability considerations, is by repositioning them as vibrant disciplines of study that relate to or elucidate contemporary concerns and debates. In order to achieve this, we must place greater emphasis on the manner of instruction and presentation, the âhowâ, than on the content, the âwhatâ, so that history will be perceived of as a purposeful reflective activity and not mindless drill and fact.KEY WORDS: history of education, teacher education, literature, John Dewey, reflective practice, self-study, and teacher induction.About the Author: Dr. Theodore Michael Christou is a Lecturer and Assistant Professor at the Faculty of Education UNB (University of New Brunswick), Office 311-1A, PO Box 4400, Fredericton, NB Canada. She can be reached at: tmc@unb.caHow to cite this article? Christou, Theodore Michael. (2010). âThat Which Has Been Bequeathed to Us: Stories in Educational Historiesâ in TAWARIKH: International Journal for Historical Studies, Vol.1(2) April, pp.169-178. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia], ISSN 2085-0980. Chronicle of the article: Accepted (February 22, 2010); Revised (March 27, 2010); and Published (April 28, 2010).